PORTFOLIO INVESTMENT ANALYSIS ON THE BASIS OF THE BLACK-LITTERMAN MODEL - G. Isavnin, Alexey; R. Galiev, Damir; N. Karamyshev, Anton; I. Makhmutov, Ilnur (Gênero & Direito, 2019)
The works of Markowitz, Tobin, Sharp in the field of portfolio investment theory are awarded the Nobel Prize in economics. The popularity of these models is explained by their mathematical simplicity and logical harmony. But these models require accurate knowledge of the statistical features of assets and use assumptions about ideal market behavior. A large number of questions immediately arise on how to evaluate the input parameters of these models in the practical use of these models. In the Black-Litterman model, an attempt is made to combine the theory of equilibrium in the capital market with the subjective opinions of analysts regarding the expected return on assets and their relationship to each other. The Black-Litterman model makes it possible to combine the theory of market equilibrium and the subjective opinions of investors about asset behavior in the market. The result is a diversified portfolio with a subjective opinion on the situation. This model is a new word in portfolio theory, which is relatively complex and focused on professionals. Due to the Bayesian approach, it is formed a new, more realistic mixed estimate of expected returns, taking into account the opinions of expert analysts. In Western literature, the Black-Litterman model is recognized as an important and powerful tool in the process of portfolio investment management. In particular, the work discusses in detail the issues of collecting, analyzing and preparing expert opinions. The ability to take into account the expert assessments is the main advantage of this model over all others